An Objective Nature of the Goodness in Lvov-Warsaw School - Pacewicz, Grzegorz (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
The thesis that goodness and truth have objective and absolute nature is a solid feature of philosophers included to Lvov-Warsaw School. There are presented and analyzed critical arguments against thesis that goodness has relative and subjective nature formulated by Kazimierz Twardowski, Władysław Tatarkiewicz and Tadeusz Czeżowski. Apart from it there are described positive arguments for thesis the goodness is objective and absolute. In the end standpoinst of three philosophers